Hemoptysis from the perspective of people with cystic fibrosis. (1st January 2020) - Romàn, Christina M.; Loughlin, Holly C.; Aliaj, Enid; Fay, Robert J.; Tran, Quynh T.; Borowitz, Drucy
Abstract: Introduction: People with cystic fibrosis (CF) are living longer, thus complications associated with age, such as hemoptysis, are increasing. The Institute of Medicine has emphasized the importance of patient‐centeredness. Although guidelines about hemoptysis in people with CF are available, these focus on management of the complication and not the patient perspective. Objective: We sought to understand hemoptysis from the point of view of those who have experienced it. Methods: We fielded an 11‐question survey to adults with CF and asked those who had hemoptysis to respond. Four questions had open‐ended options: (1) the person's first experience with hemoptysis, (2) how that experience affected the way they approach their CF, (3) how they deal with hemoptysis when it occurs outside the home and (4) a free text box for general comments. Results: Thirty‐one of 132 adults with CF who were sent a survey completed it (23% response rate); 63% F), indicated that they had experienced hemoptysis and described their triggers. In response to open questioning, 77% of respondents found their first experience with hemoptysis to be 'scary, ' 'frightening, ' 'worrying' or 'jarring.' Half of respondents reported quality of life being negatively affected by worsening stress or anxiety, fear of bleeding in public or other life impacts. Conclusions: Focusing on how to cope with future episodes of hemoptysis and the associated anxiety can be helpful to patients. Proactive communication and sensitivity to patient experience may deepen physician‐patient rapport, increase self‐efficacy to cope with future episodes and lead to more comprehensive care of hemoptysis.